Optimizing Children’s Creativity through Drawing Activities and Its Implications for Cognitive Development - Nina Nursetia Ningrum; Juju Masunah; Zakaria S Soeteja; Nanang Ganda Prawira (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study explores the effects of drawing-based media stimulation on the creativity and cognitive development of early childhood learners. Using a descriptive qualitative approach, the research was structured in two phases: the first conducted prior to any form of intervention, and the second carried out after the introduction of stimulus-based images aligned with thematic learning materials. The analysis revealed a significant enhancement in various creative and cognitive indicators. Children demonstrated a broader diversity of ideas, greater spontaneity in expressing visual concepts, and a more confident use of varied colors to represent emotions, forms, and imaginative scenes. Additionally, their visual accuracy and coherence improved noticeably, especially in depicting objects or themes previously presented by the teacher. Beyond technical improvements, the findings indicate that drawing activities function as multidimensional learning tools. They encourage children to engage in reflective thinking, strengthen memory recall, and support the development of early symbolic understanding. Drawing also provides a low-pressure environment where children can construct meaning, externalize thoughts, and exercise problem-solving skills through experimentation with shapes, lines, and compositions. Overall, this study affirms that drawing-based stimulation is not merely an artistic activity but a pedagogical medium that nurtures cognitive growth, emotional expression, and foundational intellectual development during early childhood.